Death, disability, and the superhero : the Silver Age and beyond - Alaniz, José (University Press of Mississippi, 2014)
The Thing. Daredevil. Captain Marvel. The Human Fly. Drawing on DC and Marvel comics from the 1950s to the 1990s and marshaling insights from three burgeoning fields of inquiry in the humanities--disability studies, death and dying studies, and comics studies--José Alaniz seeks to redefine the contemporary understanding of the superhero. Beginning in the Silver Age, the genre increasingly challenged and complicated its hypermasculine, quasi-eugenicist biases through such disabled figures as Ben Grimm/The Thing, Matt Murdock/Daredevil, and the Doom Patrol. Alaniz traces how the superhero beca.